Determination of Chlorinity of Water without the Use of Chromate Indicator - Tae-Kee Hong; Myung-Hoon Kim; Myung-Zoon Czae (International Journal of Analytical Chemistry)
A new method for determining chlorinity of water was developed in order to improve the old method by alleviating the environmental problems associated with the toxic chromate. The method utilizes a mediator, a weak acid that can form an insoluble salt with the titrant. The mediator triggers a sudden change in pH at an equivalence point in a titration. Thus, the equivalence point can be determined either potentiometrically (using a pH meter) or simply with an acid-base indicator. Three nontoxic mediators (phosphate, EDTA, and sulfite) were tested, and optimal conditions for the sharpest pH changes were sought. A combination of phosphate (a mediator) and phenolphthalein (an indicator) was found to be the most successful. The choices of the initial pH and the concentration of the mediator are critical in this approach. The optimum concentration of the mediator is ca. 1~2 mM, and the optimum value of the initial pH is ca. 9 for phosphate/phenolphthalein system. The method was applied to a sample of sea water, and the results are compared with those from the conventional Mohr-Knudsen method. The new method yielded chlorinity of a sample of sea water of (17.58 ± 0.22) g/kg, which is about 2.5% higher than the value (17.12 ± 0.22) g/kg from the old method.